In Vitro Antiviral Effect and Potential Neuroprotection of Salvadora persica L. Stem Bark Extract against Lipopolysaccharides-Induced Neuroinflammation in Mice: LC-ESI-MS/MS Analysis of the Methanol Extract - Reem Binsuwaidan; Walaa A. Negm; Engy Elekhnawy; Nashwah G. M. Attallah; Eman Ahmed; Sameh Magdeldin; Ehssan Moglad; Sally Abdallah Mostafa; Suzy A. El-Sherbeni (MDPI AG, 2023)
Neuroinflammation is a serious immunomodulatory complex disorder that causes neurological and somatic ailments. The treatment of brain inflammation with new drugs derived from natural sources is a significant therapeutic goal. Utilizing LC-ESI-MS/MS analysis, the active constituents of Salvadora persica extract (SPE) were identified tentatively as exerting antioxidant and anti-inflammatory effects in natural medicine. Herein, we determined the antiviral potential of SPE against herpes simplex virus type 2 (HSV-2) using the plaque assay. HSV-2 is a neurotropic virus that can cause neurological diseases. SPE exhibited promising antiviral potential with a half-maximal cytotoxic concentration (CC50) of 185.960 ± 0.1 µg/mL and a half-maximal inhibitory concentration (IC50) of 8.946 ± 0.02 µg/mL. The in vivo study of the SPE impact against lipopolysaccharide (LPS)-induced neuroinflammation was performed using 42 mice divided into seven groups. All groups were administered LPS (0.25 mg/kg) intraperitoneally, except for the normal and SPE groups 1 and 2. Groups 5, 6, and 7 received 100, 200, and 300 mg/kg SPE. It was revealed that SPE inhibited acetylcholinesterase in the brain. It increased superoxide dismutase and catalase while decreasing malondialdehyde, which explains its antioxidative stress activity. SPE downregulated the gene expression of the inducible nitric oxide synthase, as well as the apoptotic markers (caspase-3 and c-Jun). In addition, it decreased the expression of the proinflammatory cytokines (interleukin-6 and tumor necrosis factor-alpha). Mice administered SPE (300 mg/kg) with LPS exhibited normal neurons in the cerebral cortices, hippocampus pyramidal layer, and cerebellum, as determined by the histopathological analysis. Therefore, using S. persica to prevent and treat neurodegeneration could be a promising new therapeutic strategy to be explored.